The major risk factor for depression in the Chinese middle-aged and elderly population: A cross-sectional study - Ni, Xiaolin; Su, Huabin; Lv, Yuan; Li, Rongqiao; Chen, Chen; Zhang, Di; Chen, Qing; Zhang, Shenqi; Yang, Ze; Sun, Liang; Zhou, Qi; Zhu, Xiaoquan; et al. (Frontiers in Psychiatry, 2022)
Background: The number of patients suffering from depression is continuously increasing in China. Demographic characteristics, physical health levels, and individual lifestyles / healthy behaviors are associated with the severity of depression. However, the major risk factor for depression remains unclear. Methods: In this investigation, 16512 patients were screened using the CHARLS (China Health and Retirement Longitudinal Study) database after being determined to be eligible based on the inclusion criteria. Depressive symptoms were evaluated through the CESD-10 (10-item Center for Epidemiological Studies Depression Scale). Consequently, various models were developed based on potential predictive factors, employing stepwise LR (Logistic Regression) / RF (Random Forests) models to examine the influence and weighting of candidate factors that affect depression. Results: Gender, residential address location, changes in health status following last interview, physical disabilities, chronic pain, childhood health status, ADL (activity of daily living), and social activity were all revealed to be independent risk factors for depression (p<0.05) in this study. Depression has a synergic effect (across chronic pain and age groups). In comparison to other factors, RF results showed that chronic pain had a stronger impact on depression. Conclusion: This preliminary study reveals that chronic pain is a major risk factor for depression.